DIE VERHAAL VAN AFRIKAANSE CHRISTENVROUE: UITNODIGING TOT MORELE VORMING - Mouton, Elna (Scriptura, 1997)
The essay briefly explores the nature and influence of three formative stories within the biography of Afrikaans Christian women: their relation of family/friends, society, and the Bible/church. These stories collectively determine and reflect the identity and ethos not only of Christian women, but of the church at large, and even more basically, the church’s understanding of God. In conclusion, some strategic suggestions are made from within reformist feminist discourse, focusing on the urgent challenge regarding the formation of moral agency in terms of the transformative potential of Scripture (with the epistle to the Ephesians as a case study).